High prevalence of bronchiectasis in emphysema-predominant COPD patients - Dou, Shuang; Zheng, Chunyan; Cui, Liwei; Xie, Mengshuang; Wang, Wei; Tian, Hui; Li, Kang; Liu, Kaidi; Tian, Xinyu; Wang, Xin; Zhang, Qun; Ai, Xin; et al. (International journal of chronic obstructive pulmonary disease, 2018)
COPD has been identified as an etiology or related disease of bronchiectasis, and bronchiectasis has been classified as a comorbidity of COPD. In this study, we investigated the prevalence of bronchiectasis in different phenotypes of COPD subjects and the correlation between bronchiectasis and different phenotypes, especially emphysema. COPD patients were recruited from April 2012 to December 2015. The presence of bronchiectasis and related information were statistically analyzed. COPD subjects were separated into subgroups in two ways: COPD with and without bronchiectasis groups and emphysema-predominant (emphysema index, EI≥9.9%) and non-emphysema-predominant (EI<9.9%) groups. In total, 1,739 COPD patients were incorporated into the study, among which 140 cases (8.1%) were accompanied with radiological bronchiectasis. COPD patients with concomitant bronchiectasis presented worse pulmonary function (FEV % predicted, <0.001), higher EI (15.0% vs 13.4%, <0.001), and higher proportion of pulmonary hypertension and cor pulmonale (6.4% vs 2.4%, =0.005 and 23.6% vs 16.1%, =0.022) than patients without bronchiectasis. Of all the COPD patients, 787 with EI data were divided into emphysema-predominant (n=369) and non-emphysema-predominant groups (n=418). The proportion of bronchiectasis was 16.5% and 10.3% ( =0.01), respectively. Severity of bronchiectasis increased as the degree of airflow limitation ( =-0.371, <0.001) and emphysema increased ( =0.226, =0.021). After adjusting confounding factors, FEV % predicted (OR, 1.636; 95% CI, 1.219-2.197; =0.001) and EI (OR, 1.993; 95% CI, 1.199-3.313; =0.008) were significantly related with the presence of bronchiectasis in COPD patients. The proportion of bronchiectasis is higher in emphysema-predominant COPD subjects. Emphysema measured by EI and FEV % predicted are independent predictors for bronchiectasis in COPD subjects, while the underlying mechanism deserves further investigation.